Urban transport and the environment an international perspective (Emerald, 2004)
The damaging environmental impact of urban transport, as recognised by the Kyoto Protocol to the UN Framework Convention on Climate Change, is a worsening global problem that needs to be tackled with local solutions. At the same time, urban transport has been causing serious local environmental problems, particularly in developing countries. This book was commissioned with the aim of helping to develop solutions by sharing experience from around the world. Four extensive chapters by leading researchers give an overview of the problem, analyse structures and trends in urban transportation, list the various ways transport affects the environment, and critically review the whole range of policy countermeasures available. The second half of the volume is given over to a uniquely valuable collection of case studies of 21 metropolises, carefully selected to provide a cross-section of different types of city from across the developing and developed world. The relevant characteristics of these cities are systematically described: socio-economic background; local condition of transport and the environment; policy planning, implementation, and evaluation, all with concrete examples. Key data are then presented in charts with a common structure to facilitate comparisons between cities.